HIDROGEOKIMIA AIRTANAH PADA DAERAH PANTAI: STUDI KASUS DATARAN RENDAH KATAK, DESA SUMBER AGUNG, KABUPATEN BANYUWANGI - Arief Nur Muchamad; Boy Yoseph CSS Syah Alam; Euis Tintin Yuningsih (Indonesian Institute of Sciences, 2017)
This paper describes the groundwater quality assessment conducted in Katak lowland area, in Banyuwangi District, East Java. The quality of water salinity had been identified during field observation. In order to identify the origin of saline groundwater, a hydrogeochemical study has been carried out by analysing of 12 groundwater wells, 3 surface water and sea water. Hydrogeochemical analysis identified major ion elements on Piper′s diagram to know the facies and dominant ion content in ground water study area. The interpretation of plots for different major ions suggests that saline water in Katak are typically salt water intrusion and flushing salt residue in marine sediment/limestone. This hydrochemical research area provides new insights into the geochemical relationships between freshwater and seawater at different depths in coastal and alluvial sediments. Saltwater intrusion occurs due to cone of depression caused by concentrated exploitation of groundwater in the south/coastal area, and flushing mainly by groundwater flow through marine sediment/limestone in the northern area. Groundwater zonation is characterized by hydrochemical type from natrium chloride type in the southern area to calciumsulphate type in the northern area. Controlled by hydrodynamic of groundwater with salt water and flushing of geochemical by ground water, respectively. AbstrakMakalah ini menjelaskan hasil dari penilaian kualitas airtanah yang dilakukan di daerah dataran rendah Katak, di Kabupaten Banyuwangi, Jawa Timur. Kualitas airtanah yang asin telah teridentifikasi saat observasi lapangan. Dalam rangka mengidentifikasi asal air asin di daerah Katak, studi hidrogeokimia dilakukan terhadap sampel airtanah dari 12 airtanah sumur/bor, 3 air permukaan dan air laut. Analisis hidrokimia dilakukan dengan pengeplotan unsurunsur ion utama pada diagram Piper untuk mengetahui fasies dan kandungan ion dominan pada airtanah di daerah penelitian. Interpretasi plot untuk ion utama menunjukkan bahwa salinitas di daerah Katak diakibatkan oleh intrusi air laut dan pembilasan garam-garam pada sedimen marine/batugamping. Penelitian hidrokimia di daerah dataran rendah Katak memberikan wawasan baru mengenai hubungan antara air tawar dan air laut pada kedalaman yang berbeda di dalam sedimen pantai dan aluvial. Intrusi air asin terjadi karena kerucut depresi yang disebabkan oleh eksploitasi air tanah terkonsentrasi di bagian selatan yang merupakan daerah pesisir dan pembilasan karena aliran air tanah melalui sedimen marine/batugamping di Utara. Zonasi jenis airtanah diketahui dari karakteristik hidrokimianya, mulai dari jenis natrium klorida di Selatan sampai kalium sulfat di Utara. Hal tersebut masing-masing dikontrol oleh hidrodinamika airtanah dengan air asin dan pelarutan kimia batuan oleh airtanah.